Perbandingan Konsep Khulu' dalam Hukum Islam dan Hukum Pernikahan di Indonesia - Musthafa, Alwi; Salma, Siti; syawaliana, anisa; Hafidzi, Anwar (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract Marriage is one of the main aspects of social life. However, marriage is not always smooth and can end in divorce. In Islam, one type of divorce that a wife can carry out is khulu', which means the wife voluntarily redeems herself from the marriage by paying iwad to her husband. On the other hand, marriage law in Indonesia regulates several types of divorce such as talak and divorce. This research aims to compare the concept of khulu' in Islamic law with the concept of divorce in marriage law in Indonesia. This research uses a qualitative research method with a comparative approach. Research data was obtained from literature studies and documentation related to khulu' and divorce in Indonesia. The similarities found are the existence of a religious legal basis, the existence of certain conditions, and the existence of legal consequences. And differences exist in terms of definitions, implementation procedures, and women's rights. These similarities and differences are caused by several factors, such as religious, cultural, social and legal factors. Keywords: Khulu', Divorce, Islamic Law, Marriage Law, Indonesia Keywords: marital satisfaction, husband's turn distribution, hadisth Abstrak Pernikahan merupakan salah satu aspek utama dalam kehidupan bermasyarakat. Namun, pernikahan tidak selalu mulus dan dapat berujung pada perceraian. Dalam Islam, salah satu jenis perceraian yang dapat dilakukan oleh istri adalah khulu', yang artinya istri secara sukarela menebus dirinya dari pernikahan dengan membayar iwad kepada suami. Disisi lain, hukum pernikahan di Indonesia mengatur beberapa jenis perceraian seperti talak dan cerai gugat. Penelitian ini bertujuan untuk membandingkan konsep khulu' dalam hukum Islam dengan konsep perceraian dalam hukum pernikahan di Indonesia. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan komparatif. Data penelitian diperoleh dari studi literatur dan dokumentasi terkait dengan khulu' dan perceraian di Indonesia. Persamaan yang ditemukan adalah adanya dasar hukum agama, adanya syarat-syarat tertentu, dan adanya akibat hukum. Dan perbedaan ada dalam hal definisi, tata cara pelaksanaan, dan hak-hak perempuan. Persamaan dan perbedaan tersebut disebabkan oleh beberapa faktor, seperti faktor agama, budaya, sosial, dan hukum. Kata Kunci: Khulu', Perceraian, Hukum Islam, Hukum Pernikahan, Indonesia